Melanogenesis in freckles patients analysis in facultative color of Melayu ethnic with skin phototype IV & V - Catharina Sagita, Catharina Sagita (Universitas Gadjah Mada, 2004)
Background: Patients with lack of DNA repair capacity syndrome prone to have skin cancers and usually have freckles on their skin. Freckles is considered as a risk factor for skin cancer. Repair of sun induced DNA damage was proved to stimulate melanogenesis. The difference of melanogenesis capacity between freckles and non freckles peoples has never been studied.Objective: To determine the difference of melanogenesis capacity between freckles and non freckles patients by measuring the difference of facultative-constitutive skin color in Melayu peoples with skin ptohotype IV-V.Method: A case control study was performed to determine the difference of melanogenesis capacity between 31 freckles subjects and 32 non freckles subjects.Result: There was no significant difference (p> 0.05) in melanogenesis capacity between freckles and non freckles subjects.Conclusion: There is no difference of melanogenesis respon between freckles and non freckles patient.Key words: freckles, melanogenesis, skin color, IV-V phototype skin